Evaluation of chronic hepatitis B patients who voluntarily discontinued oral antiviral therapy: is there an answer to the controversial topic? - Arslan, Eyup; Yildiz, Yesim; Karasahin, Omer; Demir, Yakup; Mermutluoglu, Cigdem Tumbul; Unlu, Gulten; Celen, Mustafa Kemal (Lippincott Williams & Wilkins, 2024)
ObjectiveThe uncertain treatment duration for nucleos(t)ide analogues (NA) used in the treatment of chronic hepatitis B (CHB) is an important problem for both patients and physicians. The aim of this study was to evaluate the determinants of virologic relapse (VR) and the optimum time of treatment discontinuation in the follow-up of CHB patients who voluntarily discontinued treatment after virological suppression was achieved under NA use.MethodsData from 138 patients from 11 centers were included in this registry-based study. Factors associated with VR were investigated using multivariate Cox regression analysis.ResultsNinety-nine (71.7%) of the patients were HBeAg (Hepatitis B e antigen) negative. During the 24-month follow-up period after treatment discontinuation, VR occurred in 58.7% (n = 81) of all patients and 57.6% (n = 57) of HBeAg-negative patients. The duration of NA treatment was significantly shorter (cutoff 60 months) in HBeAg-negative patients who later developed VR. In addition, the duration of virologic remission achieved under NA treatment was significantly shorter (cutoff 52 months) in those who later developed VR. In the Cox multivariate regression model of HBeAg-negative patients, having less than 60 months of NA treatment (HR = 2.568; CI:1.280-5.148; P = 0.008) and the levels of alanine aminotransferase being equal to or higher than twice the upper level of normal at the beginning of treatment (HR = 3.753; CI:1.551-9.081; P = 0.003) were found to be statistically significant and independently associated with VR.ConclusionThe findings of this study may provide clinical guidance in terms of determining the most appropriate discontinuation time for NA.
Keywords: hepatitis B; nucleos(t)ide analogue; treatment discontinuation; treatment duration; virologic relapse